Toxoplasma Encephalitis in Haitian Adults with Acquired Immunodeficiency Syndrome: A Clinical-Pathologic-CT Correlation - Post, M. Judith Donovan; Chan, Joseph C.; Hensley, George T.; Hoffman, Thomas A.; Moskowitz, Lee B.; Lippmann, Susan (American Journal of Neuroradiology, 1983)
The clinical data, histologic findings, and computed tomographic (CT) abnormalities in eight adult Haitians with toxoplasma encephalitis were analyzed retrospectively. Diagnosis was established by identification of Toxoplasma gondii on autopsy in five and brain biopsy in three specimens and subsequently confirmed by the immunoperoxidase method. All these patients, six of whom had been in the United States for 24 months or less, had severe idiopathic immunodeficiency syndrome. All were lymphopenic and six were on treatment for tuberculosis when the toxoplasma encephalitis developed. All patients were studied with CT when they developed an altered mental status and fever associated with seizures and/or focal neurologic deficits. Scans before treatment showed multiple intraparenchymal lesions in seven and a single lesion in the thalamus in one. Ring and/or nodular enhancement of the lesions was found in six and hypodense areas in two. Progression of abnormalities occurred on serial studies. These CT findings that were best shown on axial and coronal thin-section double-dose contrast studies were useful but not diagnostically pathognomonic. In patients with similar clinical presentation CT is recommended to identify focal areas of involvement and to guide brain biopsy or excision so that prompt medical therapy of this often lethal infection can be instituted.